The effects of sustained manual pressure stimulation according to Vojta Therapy on heart rate variability - Opavsky, Jaroslav; Slachtova, Martina; Kutin, Miroslav; Hok, Pavel; Uhlir, Petr; Opavska, Hana; Hlustik, Petr (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
BACKGROUND: The physiotherapeutic technique of Vojta reflex locomotion is often accompanied by various autonomic activity changes and unpleasant sensations. It is unknown whether these effects are specific to Vojta Therapy. Therefore, the aim of this study was to compare changes in cardiac autonomic control after Vojta reflex locomotion stimulation and after an appropriate sham stimulation. METHODS: A total of 28 young healthy adults (20.4 - 25.7 years) were enrolled in this single-blind randomized cross-over study. Participants underwent two modes of 20-minute sustained manual pressure stimulation on the surface of the foot on two separate visits. One mode used manual pressure on the lateral heel, i.e., in a zone employed in the Vojta Therapy (active stimulation). The other mode used pressure on the lateral ankle (control), in an area not included among the active zones used by Vojta Therapy and whose activation does not evoke manifestations of reflex locomotion. Autonomic nervous system activity was evaluated using spectral analysis of heart rate variability before and after the intervention. RESULTS: The active stimulation was perceived as more unpleasant than the control stimulation. Heart rate variability parameters demonstrated almost identical autonomic responses after both stimulation types, showing either modest increase in parasympathetic activity, or increased heart rate variability with similar contribution of parasympathetic and sympathetic activity. CONCLUSION: The results demonstrate changes of cardiac autonomic control in both active and control stimulation, without evidence for a significant difference between the two.
Keywords: reflexní terapie; autonomní nervový systém; heart rate variability; noha (od hlezna dolů); Healthy Volunteers; Cross-Over Studies; reflex locomotion; Single-Blind Method; mužské pohlaví; jednoduchá slepá metoda; tlak; Pressure; Adult; mladý dospělý; Heart Rate; srdeční frekvence; Foot; spectral analysis; Young Adult; ženské pohlaví; Physical Stimulation; Reflexotherapy; Humans; Autonomic Nervous System; fyzikální stimulace; klinické křížové studie; dospělí; Female; Vojta Therapy; Respiratory Rate; pressure stimulation; dechová frekvence; lidé; Male; zdraví dobrovolníci pro lékařské studie